Penerapan Edukasi Kesehatan Tentang Kebutuhan Nutrisi Pada Ibu Dengan Kehamilan Anemia - Ni Made Risma Dewi; Riski Oktafia; Eny Hernani (Jurnal Sains dan Kesehatan, 2023)
Anemia in pregnancy is a condition where the hemoglobin level is less than 11.0 g/dl. Anemia in pregnant women can harm the mother and fetus during pregnancy. Mothers with anemic pregnancies need good knowledge to meet nutritional needs during pregnancy. Pregnant women with good knowledge about pregnancy nutrition as an effort to prevent and complications from anemia with pregnancy. The purpose of this study was to describe the effectiveness of providing health education using a booklet about nutritional needs on the level of knowledge in women with anemic pregnancies. This research method uses a case study approach with a sample of this study is 1 pregnant woman with anemia. The measurement instrument used the Nutrition Needs Knowledge Questionnaire in Pregnant Women, with pre-post intervention. Intervention of implementing health education through booklet media about the nutritional needs of women with anemic pregnancies for 3 days with a duration of 10-15 minutes. The results showed that there was an increase in knowledge about nutritional needs in mothers with anemic pregnancies by 40.53%, with an average pretest score of 61.67% to 86.67% in the posttest. Conclusion: Health education through booklet media about the nutritional needs of mothers with anemia is effective in increasing knowledge of pregnant mother.